Materiais híbridos condutores baseados em grafeno/polímero visando aplicações em monitoramento e remediação de poluentes ambientais - Facure, Murilo Henrique Moreira (Universidade Federal de São Carlos, 2018)
Graphene is a material composed of a single layer of carbon atoms arranged in rings of six atoms with sp2 hybridization. Graphene displays a high sensitivity towards several molecules. Additionally, graphene presents other interesting features such as high electrical and thermal conductivity, mechanical strength and chemical stability, being considered a material with high potential for several technological applications. Herein, graphene-based and polymer-based materials were produced and used as constituents of sensing units of an electronic tongue in analyzes of organophosphorus pesticides and in pollutants remediation platforms based on the adsorption of methylene blue dye in aqueous solution. Graphene-based materials were obtained by chemical reduction of graphene oxide, which was synthesized using the modified Hummers method. The materials' physicochemical characterization was performed using Fourier transform infrared (FTIR) and UV–vis absorption spectroscopy and the morphology was analyzed using Scanning Transmission Electron Microscopy (STEM) images. The sensing units of the electronic tongue were obtained by using reduced graphene oxide (rGO) and nanocomposites obtained by the combination of the rGO with poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS), polypyrrole and gold nanoparticles. The data were treated by Principal Component Analysis (PCA). The system was able to discriminate solutions of OP pesticides at nanomolar concentrations, solutions with the mixture of these pesticides and real samples, presenting a direct relationship between the pesticide concentrations and the values of the principal components in the PCA plots. The materials employed provided sensing units with a high specific surface area and high conductivity, yielding the development of a sensor with high sensitivity. In another work, a nanocomposite made of rGO and poly(methylmethacrylate) nanofibers, produced by the Solution Blow Spinning (SBS) technique, was employed in the adsorption of the methylene blue dye. The dye adsorption kinetics and isotherm follow the pseudo-second-order and the Langmuir models, respectively. The results suggest that the adsorption capabilities of the membrane obtained are due to the synergistic effect of the strong π–π stacking interactions between the dye and the rGO combined with the properties of the electrospun nanofibers, such as high porosity and high-specific surface area per unit mass.
Conducting hybrid materials based on graphene/polymer aiming at applications in monitoring and remediation of environmental pollutants
Keywords: Óxido de grafeno reduzido; Língua eletrônica; Pesticidas organofosforados; Adsorção; Nanofibras; Reduced graphene oxide; Electronic tongue; Organophosphorus pesticides; Adsorption; Nanofibers; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES